2022
DOI: 10.1007/s11864-022-01032-5
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Prophylaxis and Treatment in Acute Leukemias

Abstract: Opinion statementImprovements in systemic therapy in the treatment of acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) have improved patient outcomes and reduced the incidence of CNS relapse. However, management of patients with CNS disease remains challenging, and relapses in the CNS can be difficult to salvage. In addition to treatment with CNS-penetrant systemic therapy (high-dose methotrexate and cytarabine), intrathecal prophylaxis is indicated in all patients with ALL, however is not u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Also, for Ara-C, studies with liposomal encapsulation of Ara-C demonstrated efficacy in patients with glioma and leptomeningeal metastasis [67]. Nonetheless, high systemic doses will lead to side effects that can be avoided by intrathecal administration which have an established safety profile for CNS metastasized tumor entities [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, for Ara-C, studies with liposomal encapsulation of Ara-C demonstrated efficacy in patients with glioma and leptomeningeal metastasis [67]. Nonetheless, high systemic doses will lead to side effects that can be avoided by intrathecal administration which have an established safety profile for CNS metastasized tumor entities [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In search of alternative inductors of apoptosis, we identified MTX and Ara-C as suitable candidates. Both cytostatics are already in clinical use for intrathecal administration in patients with meningeosis carcinomatosa or leukaemia, as well as for primary central nervous system (CNS) lymphomas [19][20][21]. Therefore, their safety profile for direct CNS application has been well established.…”
Section: Resistance To Apoptosismentioning
confidence: 99%
“…However, compared with the number of patients with APL exhibiting CR and long-term survival, the number of patients experiencing relapse is almost negligible. To date, at least to the best of our knowledge, no relevant clinical trials have been launched including such patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…As is known, CNS leukemia is a common complication associated with the treatment of acute leukemia, particularly in acute lymphoblastic leukemia (ALL). Te therapeutic options include intrathecal chemotherapy (by lumbar puncture or Ommaya reservoirs), high-dose Ara-C or MTX chemotherapy, total brain and spinal cord irradiation, and even CAR T-cells for B-cell ALL [22]. Tese treatments may be used for patients with APL with CNS leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Shokat and colleagues demonstrated that RapaLink molecules are brain-penetrant, and that it is possible to confine pharmacological activity to the central nervous system (CNS) by combination dosing with a brain-impermeant rapamycin analog known as RapaBlock (58). This finding has potential relevance for improving maintenance therapy in B-ALL, which usually includes CNS prophylaxis (59)(60)(61).…”
Section: Ruxolitinib Trialsmentioning
confidence: 99%